Bending Deformation Behavior of Aluminium Extruded Various Sections with Laminated Elastic Mandrel on Draw Bending. (2015) - Okude, Y.; Yoshihara, S.; Saito, A.; MacDonald, B.J.
Abstract: During draw bending process of thin walled aluminum sections, undesirable deformations easily occur. To prevent and predict undesirable deformation of occurrence, it is necessary to generate much data from various forming configurations and draw bending process parameters. Therefore, it is necessary to clarify the relationship between the behavior of undesirable deformation and cross-sectional shape of workpiece. In this study, the draw bending simulations of workpiece with various cross sections were calculated by finite element analysis(FEA) to confirm the bending characteristics. And, the relationship between methods for preventing undesirable deformation and cross-sectional shape was clarified in the draw bending experiment.